Narcoterrorism di Afghanistan - Muhnizar Siagian; Tiffany Setyo Pratiwi (Indonesia Center for Middle East Studies, 2018)
The existence of Afghanistan that dubbed The Golden Cresent is the birthplace of two global terrorist groups namely the Taliban and Al-Qaeda. Nearly 70% of drug activity in Afghanistan has been strongly controlled by Taliban terrorist groups since 2007. Using narcoterrorism and non-traditional security threat conceptual frameworks, this article explains the dynamics of the development of opium production and trade in Afghanistan, the Taliban track record in the opium trade in Afghanistan and the opium trade as a non-traditional security threat in Afghanistan. This article uses descriptive analysis of data obtained from books, journals, and mass media. In this study, there are two important points that obtained. First, the opium business which is a source of funding for the Taliban group is one of the main causes of the continuing acts of terrorism in Afghanistan and a source of various transnational crimes. Second, the opium trade and terrorism are non-traditional security threats that occur due to a combination of opium trade and acts of terrorism which have implications for the internal and external areas of Afghanistan.